Obsession with Covid-19 in peruvian police and armed forces: validation of the obsession with Covid-19 scale in spanish using SEM and IRT models - Caycho-Rodríguez, Tomás (2021)
ABSTRACT The study evaluated the psychometric properties of the Spanish version of the Obsession with COVID-19 Scale (OCS) in 214 police and members of the armed forces (Mage = 29.33 years, SD = 11.28). The one-dimensionality and satisfactory reliability of OCS were confirmed with confirmatory factor analysis, Item Response Theory analysis, Cronbach’s alpha, and McDonald’s omega. The scale is useful for identifying individuals with low levels of persistent and disturbing thoughts about COVID-19. COVID-19 obsession was associated with COVID-19 fear, anxiety, and depression. The OCS is suitable for investigating the psychological impact of COVID-19 on members of the police and armed forces.